Emerging pathogens: A case of Wohlfahrtiimonas chitiniclastica and Ignatzschineria indica bacteremia. (2020) - Snyder, Samantha; Singh, Pratiksha; Goldman, John
Abstract: Wohlfahrtiimonas chitiniclastica and Ignatzschineria indica are rare causes of infection in humans and have been linked to infestation with fly larvae in open wounds. Both organisms are emerging causes of disease globally and co-infection resulting in bacteremia is rare. An 82-year-old male with bilateral lower extremity infections was hospitalized due to fall with associated right lower extremity pain. On exam, a maggot infested ulcer was identified on his right lower extremity. On day three of hospitalization, blood cultures grew gram-negative and gram-variable rods, and methicillin-resistant Staphylococcus aureus . Further analysis of the gram negative and gram variable rods revealed W. chitiniclastica and I. indica respectively. Both I. indica and W. chitiniclastica were pan sensitive to all antimicrobials tested with the exception of tetracyclines to which W. chitiniclastica was fully resistant and I. indica was intermediately sensitive. The patient was treated with two weeks of IV ceftriaxone and was discharged with plans to complete a six-week course of IV daptomycin due to MRSA bacteremia. All repeat blood cultures were negative. Until recently W. chitiniclastica and I. indica infections have been documented only in farm and feral animals. Major risk factors for infection include: poor hygiene, open wounds, peripheral vascular disease, and myiasis. Due to the rarity of infection, identification of both organisms can be difficult, therefore a high index of suspicion is required.